Occupational Stress And Burnout Among Emergency Medical Technicians A Systematic Review Of Risk Factors And Coping Strategies (The Review of Diabetic Studies, 2025)
Background: Emergency Medical Technicians (EMTs) operate in high-pressure, unpredictable environments that expose them to repeated traumatic events, heavy workloads, and organizational challenges. These demanding conditions place EMTs at heightened risk for occupational stress, burnout, and psychological distress. Despite growing research in emergency medical services, limited reviews have synthesized both the risk factors and coping strategies specific to EMT populations.Aim: This systematic review aims to identify the primary occupational and organizational risk factors contributing to stress and burnout among EMTs and to examine the coping strategies used to mitigate these challenges.Methods: Following PRISMA 2020 guidelines, a comprehensive search was conducted across PubMed, Scopus, Web of Science, PsycINFO, CINAHL, and Embase for studies published between 2015 and 2025. Eligible studies focused on EMTs and examined occupational stress, burnout, coping strategies, or mental health outcomes. A narrative thematic synthesis was performed due to heterogeneity in study designs.Results: A total of 12 studies met the inclusion criteria. The findings revealed five overarching themes: (1) occupational and organizational risk factors, including workload, traumatic exposure, and workplace violence; (2) burnout manifestations such as emotional exhaustion and depersonalization; (3) adaptive coping strategies, including problem-solving, social support, and resilience training; (4) maladaptive coping patterns, such as avoidance, denial, and substance use; and (5) the impact of coping strategies on psychological well-being and job performance. Adaptive coping was associated with reduced burnout, while maladaptive strategies intensified stress and worsened mental health outcomes.Conclusion: EMTs face considerable psychological burdens due to the nature of prehospital emergency care. The findings highlight the critical need for organizational support systems, resilience-building interventions, mental health services, and evidence-based policies aimed at reducing stress and burnout. Strengthening coping resources and improving workplace conditions can enhance EMT well-being, retention, and the overall quality of emergency medical services.